542. SARS CoV-2-Associated Multisystem Inflammatory Syndrome of Children (MIS-C) in the Washington DC Metropolitan Region. (31st December 2020) - DeBiasi, Roberta L; Smith, Karen L; Bell, Michael; Berul, Charles; Ansusinha, Emily; Bundy, Vanessa; Delaney, Meghan; Diab, Yaser; Hahn, Andrea; Hamdy, Rana F; Hanisch, Benjamin; Harik, Nada; et al.
Abstract: Background: Background: Multi-system Inflammatory Syndrome of Children (MIS-C) has recently emerged internationally as a serious inflammatory complication of SARS-CoV-2 infection with significant morbidity for the pediatric population. Methods: This observational retrospective cohort study includes 33 children meeting CDC criteria for MIS-C treated between March 15 and June 17, 2020 at Children's National Hospital in Washington DC. Clinical and demographic data were extracted from medical records and are summarized. Results: Of 33 hospitalized MIS-C patients, 42% were critically ill, and 58% were non-critically ill. The median age was 8.9 years (0.7–18.7 years). More males (58 %) than females (43 %) were represented in the MIS-C cohort. The majority (75%) of children had no underlying medical condition. Criteria for incomplete or complete Kawasaki Disease (KD) were present in 39% of patients, while an additional 9% had some features of KD. However the remaining 52% of MIS-C patients presented with other sub-phenotypes including prominent severe abdominal pain and/or nonspecific multiorgan dysfunction. 30% presented with shock requiring volume and/or inotropic support. SARS-CoV-2 antibodies were present in 61% of patients. Virus was detectable by PCR in 36% of patients. At the time of initial evaluation, 39% (13/33) of children had identified cardiac abnormalities including myocardial dysfunction (5/33; 15%), coronary ectasia (4/33; 12%), coronary aneurysm (3/33; 9%), or pericardial effusion 5/33; 15%) either alone or in combination. Cytokine profiling identified elevation of several cytokines in this cohort, including IL-6. Treatment has included intravenous immunoglobulin, aspirin, anakinra and other immunomodulatory therapies, with overall rapid response to therapy. No deaths have occurred. Conclusion: The emergence of MIS-C late in the surge of SARS-CoV-2 circulation in the Washington DC metropolitan region has added to the already significant burden of hospitalized and critically ill children in our region. A significant percentage of these children present with cardiac dysfunction and abnormalities, whether or not with KD features at presentation. Detailed characterization of immune responses and long term outcome of these patients is a priority. Disclosures: Andrea Hahn, MD, MS, Johnson and Johnson (Consultant)